Diagnostico Para Establecer La Visibilidad Del Centro Empresarial Huila e de la Cámara de Comercio del Huila (2023)
The work contains an investigation to carry out a diagnosis that contributes to better visibility and recognition in the new headquarters of Competitiveness and Business Development of the Huila Chamber of Commerce in the south of the city of Neiva “Huila e, Business Center”. The fundamental purpose of this project is to propose an analysis to improve the visibility of the Huila Business Center, of the Huila Chamber of Commerce, as well as to invite the business community of the region to get to know this important center, which was built for the service of Huila businessmen. With technological modernization and the constant evolution of digital ecosystems, it is essential that business organizations of all kinds, adapt to the environment and efficiently adopt the tools available to increase their competitiveness, thus facilitating the achievement of the proposed business and economic objectives.